Os jogos como ferramenta de aprendizagem na alfabetização em uma escola do campo - Marlandes de Fátima Evaristo (2017)
This study aims to analyze the employment and importance of games for initial reading instruction as an alternative strategy presented by the National Pact for Initial Reading Instruction at the Right Age (PNAIC) for the initial reading instruction of children up to 8 years of age. Of qualitative nature, it is a research carried out in the school years of 2014 and 2015 in a rural school, Municipal School Joaquim Galvão, located in the city of São Gonçalo do Pará-MG. Participated in the research 16 students of the 3rd year/1st cycle and the regent teacher of this class. The method used consisted of three steps from the following procedures: (i) interview with the teacher; (ii) observations on the collective and individual coordinations of the teacher in the activities related to initial reading instruction and literacy process, in order to verify if they would occur according to the guidelines of the PNAIC/RURAL, emphatically observing if the games were used as a tool for initial learning of reading and writing; (iii) creation and application of the technical product of this research, Ludic Box for Initial Reading Instruction. Among the results obtained, the following stand out: (i) the pedagogical development of the students enrolled in the 3rd year in relation to initial reading instruction and literacy through the mediation of the teacher in continuing formation in the PNAIC; (ii) the use of the games in this process and the change with respect to the didactic material used by the teacher and to the PNAIC reference, whose guidelines are based on what is recommended in the Operational Guidelines for Basic Education in Rural Schools. The results open the way to an important debate on initial reading instruction and literacy in rural schools in order to rethink educational actions that are increasingly significant and that take into account the protagonists of their construction, the students.